Valence, Policy Ideas, and the Rise of Sustainability. Issue 2 (21st November 2012) - Cox, Robert Henry; Béland, Daniel
<x xml:space="preserve">Abstract</x> This article introduces to policy studies the concept of valence, which we define as the emotional quality of an idea that makes it more or less attractive. We argue that valence explains why some ideas are more successful than others, sometimes gaining paradigmatic status. A policy idea is attractive when its valence matches the mood of a target population. Skilled policy entrepreneurs use ideas with high valence to frame policy issues and generate support for their policy proposals. The usefulness of the concept of valence is illustrated with the case of sustainability, an idea that has expanded from the realm of environmental policy to dominate discussions in such diverse policy areas as pension reform, public finance, labor markets, and energy security. As the valence of sustainability has increased, policy entrepreneurs have used the idea to reframe problems in these various policy areas and promote reforms.